Impacto del clima laboral en la eficiencia de los procesos administrativos de la Unidad Educativa réplica Nicolás Infante Díaz, año 2023 - Beltrán Anchundia, Yuri Alexandra (2025)
This research project examines the influence of the work environment on the efficiency of administrative processes at the Nicolás Infante Díaz Replica Educational Unit in Quevedo, Ecuador. The introduction states that a positive work environment is crucial for staff motivation and commitment, which impacts educational quality. The main objective is to analyze how the work environment impacts administrative efficiency during the year 2023. The methodology used combines qualitative and quantitative approaches, including surveys and interviews with administrative staff. Internal communication, job recognition, and leadership were examined, identifying significant deficiencies that affect satisfaction and productivity. The results reveal that 64% of staff perceive ineffective communication, while a high percentage feel no recognition or support from management. General dissatisfaction with working conditions and professional development opportunities was also observed. Recommendations include improving communication channels, implementing a recognition system, and fostering participative leadership. These strategies seek to create a more collaborative and motivating work environment, which in turn will optimize administrative efficiency and educational quality.